2010
DOI: 10.1248/bpb.33.1589
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunodetection of Membrane Type-1 Matrix Metalloproteinase Relevant to Tumor Malignancy with a Pre-targeting Method

Abstract: Tumor malignancy is closely associated with the poor prognosis in cancer patients. Thus, accurate and sensitive diagnosis for detecting the tumor malignancy is required to provide the optimal therapeutic regimen to the patients. Nuclear medical techniques such as single photon emission computed tomography (SPECT) and positron emission tomography (PET) are non-invasive and have the potential to provide sensitive diagnoses by detecting gamma rays emitted from a radiolabeled probe injected into the body. Thus, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…To improve the T ⁄ B ratio, we previously reported using a pre-targeting method. (24) While this modification improved the T ⁄ B ratio, the method required multiple administrations, which would be undesirable for clinical use. In this study, the newly developed 111 In-MT1-scFv and 111 In-MT1-diabody showed specific affinity for MT1-MMP hinge region and gave high T ⁄ B ratios.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the T ⁄ B ratio, we previously reported using a pre-targeting method. (24) While this modification improved the T ⁄ B ratio, the method required multiple administrations, which would be undesirable for clinical use. In this study, the newly developed 111 In-MT1-scFv and 111 In-MT1-diabody showed specific affinity for MT1-MMP hinge region and gave high T ⁄ B ratios.…”
Section: Discussionmentioning
confidence: 99%
“…After allowing sufficient time for POS to degrade in normal tissues, We also developed probes using anti-MT1-MMP antibody or its reduced-molecular-weight form for the target recognition unit and succeeded in imaging of MT1-MMP. [46][47][48][49][50][51] In addition, we performed research on structure-activity-distribution rela- tions of an asymmetric urea compound that binds to prostatespecific membrane antigen (PSMA) expressed in prostate cancer cell membrane, and developed a nuclear medical molecular imaging probe for PSMA-positive tumor. [52][53][54] We are currently preparing a clinical study using this probe.…”
Section: Molecular Imaging Of Tumorsmentioning
confidence: 99%
“…Streptavidin-conjugated anti-MT1-MMP mAb and streptavidinconjugated negative control IgG were synthesized according to a previously described method [14]. Briefly, EZ-Link® sulfosuccinimidyl-6-(biotinamido) hexanoate (sulfo-NHS-LC-biotin; Pierce, Inc.) was added to a solution of anti-MT1-MMP mAb (113-5B7, Daiichi Fine Chemical Co.) in a molar ratio of 12:1.…”
Section: Synthesis Of Streptavidin-conjugated Anti-mt1-mmp Mabmentioning
confidence: 99%
“…As the post-administration contrast agent, polyamidoamine dendrimer (PAMAM) was selected as the base structure since it is structurally well-defined and functional moieties including biotins and Gd chelates for both targeting and signal emission functions can easily be attached to the large number of its surface amino groups. The pre-targeting strategy is expected to provide selective and effective accumulation of the PAMAM-based contrast agent to the targeted site and a high S/N ratio during the first hours following administration, as has been observed in radioimmunotherapy and radioimmunodetection [13][14][15][16], and to potentially lead to lower in vivo toxicity [17,18].…”
Section: Introductionmentioning
confidence: 99%